1992
DOI: 10.1152/jn.1992.68.5.1473
|View full text |Cite
|
Sign up to set email alerts
|

Altered patterns of reflex excitability subsequent to contusion injury of the rat spinal cord

Abstract: 1. The present study investigated regulation of reflex excitability after experimental contusion injury of the spinal cord. 2. Four measures of H-reflex excitability were evaluated in normal rats and at 6, 28, and 60 days after contusion injury at the T8 level: 1) reflex thresholds, 2) slope of the reflex recruitment curves, 3) maximal plantar H-reflex/maximal plantar M-response (Hmax/Mmax) ratios, and 4) rate-sensitive depression (i.e., the decrease in reflex magnitude relative to repetition rate). 3. Tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
3
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 0 publications
9
114
3
1
Order By: Relevance
“…The precise mechanisms by which the effects of injury are distributed throughout the cord are unknown, but similar evidence was found by Yerzierski et al (14), Thomp- son et al (15) and Ruggiero et al (8). Anesthesia is not thought to affect Fos expression; the results showed an effect of surgical stress, but the greater expression of Fos protein following spinal cord contusion suggests that spinal cord injury causes an increase in Fos expression.…”
supporting
confidence: 59%
“…The precise mechanisms by which the effects of injury are distributed throughout the cord are unknown, but similar evidence was found by Yerzierski et al (14), Thomp- son et al (15) and Ruggiero et al (8). Anesthesia is not thought to affect Fos expression; the results showed an effect of surgical stress, but the greater expression of Fos protein following spinal cord contusion suggests that spinal cord injury causes an increase in Fos expression.…”
supporting
confidence: 59%
“…This reflex normally undergoes changes with a variety of rhythmic motions such as stepping, 29 walking, 30 running 31 and pedaling. 32 In animals, the H-reflex has been a valuable tool to measure changes in spinal circuitry in both contusion 20,33 and transection models. 23,24 The H-reflex has also been used to assess changes in spinal circuitry in the human, a recent effort concluding that (1) chronically paralyzed subjects showed suppression of H-reflexes to , and all statistical comparisons in this figure made against the Tx ONLY 30D group.…”
Section: Discussionmentioning
confidence: 99%
“…59 The spinal contusion model, usually evoked by dropping a weight on the exposed spinal cord, produces changes in the excitability of neurons that could be relevant to the development of pain after SCI. 60 It has been demonstrated that animals exhibit features of neuropathic pain at the level of SCI with lowered vocalization thresholds in the dermatomes adjacent to the level of injury. 48 In particular, hypersensitivity was observed for lesions restricted to the central grey matter or the dorsal half of the spinal cord, suggesting that spinal grey matter damage contributes to development of at level neuropathic SCI pain.…”
Section: Experimental Modelsmentioning
confidence: 99%